Pemahaman Aqidah Islam di Kalangan Kaum Milenial di Desa Percut Kec. Percut Sei Tuan - Hajizah Azzahra; Musaddad Lubis; Sholahuddin Ashani (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2022)
Percut Village is one of the villages in the Percut Sei Tuan sub-district, Deli Serdang Regency with an area of 1,063 hectares. When progress is considered a mecca for millennials. Millennials do not understand the values of teachings in Islam resulting in them falling into deviant teachings and not in accordance with what Islam teaches so that the millennial aqeedah declines. Looking at the condition of the reduced millennial Muslims themselves, it can be easily interpreted that the reduced Millennial Muslims are Muslims who were born in the midst of the times and in the midst of globalization. The questions in this study; 1) How is the understanding of Islamic aqidah among millennials in Percut village?; 2) What are the efforts to strengthen Islamic aqidah in Percut village?. The government of Percut Village, Percut Sei Tuan District will not miss to give great attention to all its citizens, especially millennials in order to maintain their faith/faith values. -religious institutions in fostering generations (teenagers) through religion.